A Pacific Skills Visa: Improving opportunities for skilled migration throughout the Pacific region - Satish Chand; Michael A. Clemens; Helen Dempster (Institute of Labor Economics (IZA), 2021)
The demand for skills exceeds supply, both within the Pacific Islands and the high-income countries of the Pacific Rim. Enhancing skilled migration therefore has the potential to generate large economic gains. The Global Skill Partnership is a migration model that can support such mutually beneficial mobility by moving training into the country of origin. In this paper, we outline its regional application to the Pacific. To assess the potential economic gains from such a Pacific Skills Partnership, we present new data on earnings and the cost of training in the Pacific Islands for three qualifications- accountants, computer science graduates, and chefs-and explore how such training could be financed through loan schemes. Graduates could be provided with internationally accredited qualifications and a new Pacific Skills Visa, facilitating their access to work opportunities abroad, particularly in the regions' high-income countries. This Pacific Skills Partnership could bring large economic benefits to countries of origin, destination, and the migrants themselves.
Keywords: F22; J11; J24; 330; immigration; labor; low-skill; visa; mobility; Pacific Islands; Papua New Guinea; seasonal; temporary